PENGGUNAAN MEDIA SIMULASI BISNIS DALAM PEMBELAJARAN EKONOMI PADA MATERI PRODUKSI DAN DISTRIBUSI - Irmawati; Daroe Iswatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the application of business simulation media in Economics learning on production and distribution material at MA Muhammadiyah Balassuka, and analyze its influence on students' understanding of economic concepts and entrepreneurial attitudes. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of one Economics teacher and 25 grade XI IPS students. The results of the study indicate that the use of business simulation media can increase student active engagement during the learning process. Students become more enthusiastic, creative, and brave in making economic decisions through direct experience in simulating roles as producers, distributors, and consumers. In addition to improving understanding of production and distribution concepts, this media also fosters entrepreneurial values ​​such as responsibility, cooperation, independence, and courage to take risks. Thus, it can be concluded that business simulation media is effective as an innovative learning strategy that integrates cognitive, affective, and psychomotor aspects holistically, and is relevant to the Independent Learning paradigm and the demands of 21st-century education.